PERSISTENCE OF BORDETELLA PERTUSSIS BACTERIA AND A POSSIBLE MECHANISM OF ITS FORMATION - G. I Karataev; L. N Sinyashina; A. Yu Medkova; E. G Semin (Журнал микробиологии, эпидемиологии и иммунобиологии, 2015)
A growth of pertussis morbidity is observed in many countries of the world against the background of mass vaccination. Forms of the disease course have changed. Atypical forms of pertussis occur predominately in adolescents and adults. Asymptomatic carriage of the causative agent has been established. Infection of infants with Bordetella pertussis bacteria in more than 90% of cases occurs from parents and relatives. A prolonged persistence of the causative agent has been identified. Morbidity increase in developed countries is associated with the use of acellular vaccines, that do not protect from the infection, but reduce severity of the disease. A change of genotypes of the circulating bacteria strains is observed ubiquitously. Formation of a persistent form of B. pertussis is possible due to a reversible integration of IS-elements into bvgAS operon and other virulence genes. The results of studies of invasion and survival of B. pertussis bacteria in eukaryotic cells, a change in B. pertussis bacteria population after experimental infection of laboratory mice and monkeys are presented, accumulation of avirulent insertion Bvg mutants of B. pertussis was detected. The data obtained are in accordance with the results of analysis of causative agent population in patients with typical and atypical forms of pertussis in humans. More than 50% of the population of B. pertussis bacteria in practically healthy carriers was shown to be presented by avirulent insertion Bvg mutants. B. pertussis virulence reducing as a result of inactivation of single or several virulence genes probably provide long-term persistence of bacteria in host organism and formation of apparently healthy vehicles. Follow-up studies on that front would help to formulate new attitudes to preventive measures of pertussis and lead to development of fundamentally new pharmaceuticals (vaccines) preventing formation of bacterial persistence.